Newly diagnosed immune thrombocytopenia adults: Clinical epidemiology, exposure to treatments, and evolution. Results of the CARMEN multicenter prospective cohort. Issue 6 (20th March 2017) - Moulis, Guillaume; Germain, Johanne; Comont, Thibault; Brun, Natacha; Dingremont, Claire; Castel, Brice; Arista, Sophie; Sailler, Laurent; Lapeyre‐Mestre, Maryse; Beyne‐Rauzy, Odile; Godeau, Bertrand; Adoue, Daniel; et al.
Abstract: The clinical epidemiology of immune thrombocytopenia (ITP) is not well known in adults. This study was aimed at assessing the clinical epidemiology of incident ITP adults, the factors associated with chronicity and exposure to treatments. This study was conducted in the CARMEN registry, a multicentric prospective cohort aimed at including all newly diagnosed ITP adults in the French Midi‐Pyrénées region, South of France (3 million inhabitants) from June 2013. Descriptive analyses and multivariate logistic regression models were conducted. Out of 121 newly diagnosed ITP until December 2014, 113 patients were followed in the region and gave informed consent. Median age was 65 years. Half of the patients were female, 20.3% had a secondary ITP, 50.4% had a Charlson's score ≥1, median platelet count was 17 × 10 9 /L; 50.9% had bleeding symptoms, including 2 severe gastrointestinal tract and 1 intracranial bleedings; 21.4% had another autoimmune disease and 20.3% experienced an infection within the six weeks before ITP onset. Persistency and chronicity rates were 68.2% and 58.7%, respectively. Antinuclear antibodies were associated with chronicity (OR: 2.89, 95% CI: 1.08‐7.74). Sixty‐eight (60.2%) patients were treated during the week following the diagnosis. Factors associated with the use of intravenous corticosteroids were secondary ITP and high bleeding score. Those associated with the use of intravenous immunoglobulin (IVIg) were a high bleeding score and low platelet count. In conclusion, severe bleeding is rare at ITP onset. Associated autoimmune diseases and recent infections were frequent. Antinuclear antibodies seem predictors of chronicity. Intravenous corticosteroids and IVIg were frequently used.